Macroeconomics shocks and stability in Malaysian banking system; a structural VAR model - Alizadeh Janvisloo, Mohammadreza; Muhammad, Junaina; Hassan, Taufiq (Scientific & Academic Publishing, 2013)
Negative effects of 1997 financial crisis in Malaysia, such as other emerging countries, led to the development and restructuring of financial system in this country. Hence many big firms and corporations to provide their required funds shift towards newly established markets like stock and bond markets. Under these conditions, many banks maintained their profitability by attracting new customers especially Small and Medium size Entrepreneurs (SMEs) and increased their loans and credits to the household sector. Now a significant share of loans has been given to the household sector and SMEs and this feature caused the banking system to become more vulnerable against external and internal shock. So, increasing unemployment and reducing income for any reason will be a threat for banks by Default risk. Thus, anticipated effects of macro-economic shocks on banks’ operation are more important to policy makers and bankers. Hence in this study, a Structural Vector Autoregressive (SVAR) model is employed to show how a macroeconomic shock effects on Non-Performing Loan changes (NLP) as a credit risk indictor in Malaysian commercial banking system for period of 1997-2012. The designed Model is called AB model that is limited based on IS-LM theory. According to results the demand and supply shock have negative and monetary shock has positive effects on NPL ratio. Mean while simultaneous effects of monetary and demand shocks are more than supply shocks effects but the supply shocks’ impact is more persistent. Comparison response of NPL ratio with capital ratio shows that the commercial banks against domestic shocks are safe and adequate capital to deal with the risks arising from internal shocks in the economy are considered. The results of this study can help policy makers to pursue suitable monetary policies and decrease banks failing in front of any macroeconomic shocks.